Nilai Religiusitas dan Solidaritas dalam Film Farha Karya Darin J. Sallam (Analisis Semiotika Charles Sanders Peirce) - Ramadhan, Gia; Rohanda, Rohanda; Dayudin, Dayudin (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2024)
This research analyses the social and cultural values in Darin J. Sallam's Farha by examining the relationship between Representament, Object, and Interpretant. The research uses a qualitative paradigm with a Charles Sanders Peirce semiotic analysis approach. Literature study is the method used based on data sources in the form of snippets of dialogue scenes from Farha's film published on the Netflix platform. The formal Object of this research is Charles Sanders Peirce's semiotics and the material Object is Farha Film by Darin J. Sallam. The results and discussion show several representations that can produce several interpretations. The explanation of the interpretation in this film is in the form of social and cultural values based on the theory expressed by Eduard Spranger. In this film, there are at least five social and cultural values consisting of religious, power, solidarity, theoretical, and art or aesthetic values. The various values presented in the film illustrate the setting of this film in Palestine, which at that time was hit by the Nakba Day event. The values in the film are expected to inspire many people, especially in seeing the phenomena in Palestine This research using Charles Sanders Peirce's Semiotics theory only found five social and cultural values and it is hoped that other researchers will continue this research with different theories.Keywords – Farha Film, Palestine, Peirce’s Semiotic,.